A Tailored Viro-Immunotherapy Combination Approach for the Treatment of BRCA1/2 Mutated Breast and Ovarian Cancers - Jamieson-Datzkiw, Taylor Rae (Université d'Ottawa / University of Ottawa, 2021)
Hereditary breast and ovarian cancers (HBOC) represent 5-10% of breast and 10-15% of ovarian cancer cases. These cancers tend to be aggressive and curative treatment strategies are scarce. Poly(ADP-ribose) polymerase inhibitors (PARPi), a family of drugs that inhibit DNA repair, are a promising therapy for cancers harbouring mutations in their DNA repair machinery, such as HBOC. Unfortunately, nearly all patients ultimately become resistant to PARPi, leaving limited options for definitive treatment. Oncolytic or “cancer-killing” viruses are an innovative immunotherapeutic platform capable of selectively targeting cancer cells, leaving healthy tissues unharmed. Our group has demonstrated that oncolytic rhabdoviruses may be used to deliver therapeutic payloads by encoding targeting sequences to act on genes via RNA interference. In the present work, I have engineered the oncolytic virus, vesicular stomatitis virus (VSV), to express a variety of microRNA (miRNA) sequences that target genes essential for DNA repair, sensitizing resistant cancer cells to PARPi therapy. After initial experiments revealed hurdles concerning the functionality of artificial miRNAs which specifically target BRCA1 and BRCA2 I encoded the naturally occurring hsa-miR-182 into VSV to knockdown BRCA1 and additional genes essential for DNA repair. Using a 3D spheroid model, I have demonstrated sensitization of initially resistant MDA-MB-231 breast cancer cells to the PARPi, rucaparib. Complementary work exploring the shuttling of miRNAs into small extracellular vesicles, or EVs, has also shown that we can take advantage of the EV packaging facilities in infected cells, inducing the packaging of miRNAs over-expressed by VSV (EV-miRNAs) into EVs. Future work will address the functionality of these EV-miRNAs, testing their ability to knockdown targets in uninfected cancer cells.
Keywords: Oncolytic virus